2019
DOI: 10.1002/ece3.5092
|View full text |Cite
|
Sign up to set email alerts
|

Does body size predict the buzz‐pollination frequencies used by bees?

Abstract: Body size is an important trait linking pollinators and plants. Morphological matching between pollinators and plants is thought to reinforce pollinator fidelity, as the correct fit ensures that both parties benefit from the interaction. We investigated the influence of body size in a specialized pollination system (buzz‐pollination) where bees vibrate flowers to release pollen concealed within poricidal stamens. Specifically, we explored how body size influences the frequency of buzz‐pollination vibrations. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 57 publications
9
55
0
1
Order By: Relevance
“…Our results also showed no differences in pollen amount extracted among different frequency levels. This was somewhat surprising because, recently, it has been found that larger bees that generate high floral vibration frequencies extract more pollen when compared to small bees in a given foraging effort [11], also suggesting that there may be additional effects of pollinator-specific buzzing that affect pollen removal [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also showed no differences in pollen amount extracted among different frequency levels. This was somewhat surprising because, recently, it has been found that larger bees that generate high floral vibration frequencies extract more pollen when compared to small bees in a given foraging effort [11], also suggesting that there may be additional effects of pollinator-specific buzzing that affect pollen removal [1].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other insect pollinators (e.g., Lepidoptera), buzz pollinators produce floral vibrations using their thoracic muscles and use their other body parts including mandibles, head and abdomen to release the pollen from these anthers [1,[5][6][7][8][9], an ability confined to a few insect genera. Although studies on ecology and evolutionary biology of buzz pollination have been carried out for more than a century [10], the biomechanics, pollinator physiology and behavior in relation to buzzing have only recently gained an increased interest [1,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, some bee taxa might be able to adjust their vibration velocities or duration (Harder & Barclay, 1994;Morgan et al, 2016;Russell et al, 2016), resulting in increased pollen extraction at a higher energy cost to the insect. Field observations of the large flowered S. rostratum have shown that small buzzing bees frequently visit flowers (Solís-Montero et al, 2015), but larger taxa that produce higher velocity vibrations (De Luca et al, 2019), such as Bombus and Xylocopa, are common visitors (Whalen, 1978), as well as efficient pollinators (Solís-Montero & Vallejo-Marín, 2017).…”
Section: The Influence Of Vibration Velocity On Pollen Dispensing Schmentioning
confidence: 99%
“…Similarly, the vibration properties of bees vary across and within species (King & Buchmann, 2003;Arceo-Gómez et al, 2011;Corbet & Huang, 2014;Arroyo-Correa et al, 2019;De Luca et al, 2019;Pritchard & Vallejo-Marín, 2020), and previous empirical work demonstrates that vibration properties, particularly their amplitude, affect pollen release (Harder & Barclay, 1994;King & Buchmann, 1996;. However, we know relatively little about how plant species with different anther and floral morphologies vary in their pollen release schedules (but see Harder & Barclay 1994, Dellinger et al 2019, including their response to vibrations of different amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify the differences in pollination potential, we assume that body size can be used as an indicator for pollination efficiency, thereby assuming that the larger pollinator species, B. terrestris (bumble bee), is a more effective pollinator due to its larger body size. This assumption is based on the reasoning that the ability of these types of pollinators to 'buzz pollinate', that is, to shake loose additional pollen by vibrating their wings, should become more effective with increasing body size (De Luca et al, 2019). It therefore follows, based on an average body size of 11-17 mm of a B. terrestris worker and an average body size of 8-10 mm of a male O. bicornis, that B. terrestris is, roughly, doubly as effective.…”
Section: Background and Ecological Aspectsmentioning
confidence: 99%